Pengaruh Model Pembelajaran Auditory Intelectually Repetition Berbantuan Media Cartoons Math terhadap Kemampuan Pemecahan Masalah Siswa Kelas IV SD - Aryudya Pradhita Sihsejati; Zulmi Roestika Rini (Journal on Education, 2023)
This purpose of this research was to know the effect of the AIR (Auditory, Intellectually, Repetition) learning model assisted by media cartoons math on the problem solving abilities of fourth grade students in SD Negeri Kupang 01. In this study used a quantitative Quasi-Experiment research approach. The population in this study were all fourth grade students at SDN Kupang 01 totaling 49 students and the sample was taken using a purposive sampling technique where in class IV B was the experimental class with 23 students and class IV A was the control class with 26 students. The data was analyzed by normality test, homogeneity test, simple linear regression test and independent sample t test. The results of the study: There is an influence of the application of the Auditory Intelectually Repetition learning model on the problem solving abilities of fourth grade students in SD Negeri Kupang 01 as evidenced by tcount 6.614 > ttable 2.074 and a significant value < 0.05, namely 0.000 < 0.05 using a simple linear regression test